Aplicaciones del modelo de BARBARO et al. para el cálculo de la radiación solar global por medio de estimaciones de las componentes directa y difusa, en Limón y Puntarenas, Costa Rica, para el período 1970-1972 (ING) - Wright Gilmore, Jaime (1987)
The present work uses an atmospheric model proposed by Barbaro et al., for the computation of the global solar radiation through the estimations of the direct and diffuse components, in Limón and Puntarenas, Costa Rica for the period 1970-1972. The results are presented in the form of monthly averages and compared with the observed values provided by the Meteorological Institute of Costa Rica. The percentage of error does not exceed ±8.5 per cent.It is not possible to verify the computation of the direct and diffuse components, because in Limón and Puntarenas there is not direct nor diffuse solar radiation data.In order to verify its realiability, it is recommended to apply the model to other locations equipped with actinometric stations in Costa Rica. This will allow one to predict the solar radiation on locations lacking actinometric data.